DETERMINING THE PROFITABILITY OF ISLAMIC BANKS WORLDWIDE: NET PROFIT MARGIN, NON-PERFORMING FINANCING, DEBT-TO-ASSET RATIO, AND THIRD-PARTY FUNDS - Wardana, Guntur Kusuma; Dewi, Annisa Sinta; Barlian, Noer Aisyah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study investigates the determinants of profitability in Islamic banks worldwide by examining the influence of Net Profit Margin (NPM), Non-Performing Financing (NPF), Debt-to-Asset Ratio (DAR), and Third-Party Funds (DPK) on Return on Assets (ROA). Using a quantitative descriptive approach, secondary data were collected from 20 Islamic banks across 12 countries, selected from The 100 Strongest Islamic Banks in the World by The Asian Banker for the period 2019–2023. Panel data regression with the Random Effect Model (REM) was employed after conducting Chow, Hausman, and Lagrange Multiplier tests to determine the most appropriate model. The results reveal that NPM and DAR have a significant partial effect on ROA, while NPF and DPK do not show a significant impact individually. However, collectively, the four variables significantly influence the profitability of Islamic banks, with an Adjusted R-squared of 36.24%. These findings highlight the importance for Islamic banks to enhance efficiency, manage debt structures prudently, and optimize fund allocation through productive financing in order to strengthen profitability at the global level.